Perception of Gender Issues among Surgical Residents and their Supervisors - Syed Inamullah Shah; Muzna Iftikhar; Sajida Shah; Muhammad Salman Shafique; Mahvish Noor; Jamil Ahmad Shah (Journal of Rawalpindi Medical College)
Objective: To discover attitudes and perceptions about gender related issues in surgical residents and supervisors in major teaching hospitals of twin cities.